Financial soundness of single versus dual banking system : explaining the role of Islamic banks - Nosheen (2022)
This paper empirically investigates the financial stability of the countries having both Islamic and conventional banks versus the countries having only conventional banks. It also examines the ability of Islamic banks to provide stability to the overall financial system. The analysis is carried out for a sample of 416 banks drawn from 39 countries over the period 1995–2014. The results provide sound evidence that the dual banking system is more stable than the single banking system. Higher stability is attributed to the presence of Islamic banks in the dual banking system. Furthermore, when only the dual banking system is investigated, the results strongly confirm the greater stability of Islamic banks as compared to their conventional counterparts. Although Islamic banks are mimicking conventional banking practices, their increased interactions with the real economy, investments in real assets, non-aggressive lending profile, and limited exposures to speculative activities make them more resilient and protected.